Aspek Hukum Merger dan Akuisisi Pada Lembaga Keuangan Koperasi - Permadi, I Gusti Agung Didit Eka; Wisudawan, I Gusti Agung (Fakultas Hukum Universitas Mataram, 2018)
Mergers and Acquisitions is a legal phenomenon that occurs in companies incorporated as legal entities including financial institutions. Mergers and Acquisitions aim to strengthen institutional structures and strengthen cooperative capital in the hope of improving member welfare. The legal aspects of Mergers and Acquisitions on cooperatives emphasize the legality aspect, the reasons for Mergers and Acquisitions, the processes and their legal consequences. It's just that the Acquisition in the future must be calculated and regulated in legislation because not many cooperatives are doing it Acquisition is needed as one business strategy to develop cooperatives to exist in the middle of society.